The Characteristics of The Elevator Motion Based on The Object’s Apparent Weight - Alfia Ulfa; Supeno Supeno; Singgih Bektiarso (Jurnal Pembelajaran Fisika, 2021)
This study aims to examine the characteristics of the lift motion based on apparent weight data. This type of research is quantitative research with a survey method. The results showed that the apparent weight change only occurred when the elevator started moving and just before it stopped, acceleration at the beginning of the motion and deceleration at the end of the motion. Elevator has two characteristics of motion; straight motion with constant velocity and straight motion with constant acceleration. Straight motion with constant acceleration consists of accelerated motion that occurs at the beginning of the elevator motion, and straight motion with constant acceleration slowed down at the end of the elevator motion. Meanwhile, straight motion with constant velocity occurs with a longer duration. This study's results have implications for learning physics, one of which can be used as data to develop learning resources for physics in the form of student worksheets.Keywords: Apparent weight, Elevator motion, Newton's lawDOI: http://dx.doi.org/10.23960/jpf.v9.n1.202103